High-strength hydrolysis-resistant polyurethane shoe glue and preparation method thereof

CN122898241APending Publication Date: 2026-10-13HENAN JINGHUI POLYURETHANE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611228444.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,提高硬段含量容易导致胶层脆化、柔韧性下降;传统交联体系所形成的网络结构相对单一,难以兼顾强度与耐久性;无机纳米填料则普遍存在分散稳定性不足、界面相容性较差及增强效率有限等问题;而添加型助剂以物理共混形式存在,与聚氨酯主链之间缺乏化学键合,在成膜及长期使用过程中易发生迁移、析出并随水相流失,致使抗水解功能随时间衰减而难以持久

Benefits of technology

[0023]1、本发明通过引入氟硅改性超支化胺醇交联剂参与聚氨酯分散体的多级网络构建,有效解决了传统水性聚氨酯鞋胶极性基团易吸水导致的水解降解与强度衰退问题。该交联剂借助超支化活性结构的高密度官能团特性,在固化成膜过程中与聚氨酯大分子链段发生深度扩链交联,形成空间立体网状结构,大幅提升了树脂基体的本体内聚力与机械强度;同时,交联剂结构中改性接入的含氟链段与硅氧烷链段凭借其极低的表面能特性,在成膜时能够自发向胶膜表面发生迁移富集,构建出致密的疏水屏蔽保护层。这种内部高强度交联与外部强效拒水的物理化学协同机制,切断了外部水分子的毛细渗透路径,有效阻挡了水分子对聚氨酯主链中酯键和脲键的攻击,从而实现了鞋胶长期耐水解性能的跨越式提升。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of polyurethane materials, and particularly discloses a high-strength hydrolysis-resistant polyurethane shoe glue and a preparation method thereof. The method comprises the following steps: firstly, preparing a carboxyl-containing polyurethane prepolymer by reacting a polymer polyol with diisocyanate, neutralizing, emulsifying and polyamine chain-extending to obtain a polyurethane dispersion; then, introducing a fluorosilicon-modified hyperbranched polyamine crosslinking agent to construct a multi-level crosslinking network, and adding a borate ester reinforcing agent prepared from catecholized polyether, aminobenzene boronic acid and hydrophobic nano-silicon dioxide to realize synergistic reinforcement. The fluorosilicon-modified hyperbranched polyamine crosslinking agent has fluorine-containing segments, siloxane segments and hyperbranched active structures, and the borate ester reinforcing agent has dynamic borate ester bonds, catechol groups and nano-reinforcing phases. The polyurethane shoe glue prepared by the application has excellent bonding strength, hydrolysis resistance, wet heat aging resistance and interfacial adhesion, and can meet the high-reliability bonding requirements of shoe materials under long-term service conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyurethane materials technology, and more specifically, to a high-strength, hydrolysis-resistant polyurethane shoe adhesive and its preparation method. Background Technology

[0002] Polyurethane shoe adhesives, due to their high bonding strength, good flexibility, and strong adaptability to various shoe material substrates, have become one of the most widely used adhesives in the footwear manufacturing industry. With increasingly stringent environmental regulations and the popularization of green manufacturing concepts, water-based polyurethane shoe adhesives, due to their low volatile organic compound content, safe application, and low pollution, are gradually replacing traditional solvent-based products and becoming the mainstream direction of industry development. However, footwear products often undergo prolonged exposure to sweat, washing, moisture, and alternating temperature and humidity during actual service, placing high demands on the hydrolysis resistance and long-term bonding reliability of the shoe adhesives.

[0003] Waterborne polyurethane shoe adhesives typically use polyester polyols, polyether polyols, or polycarbonate polyols as soft segment components, with the main structure constructed via diisocyanate chain extension. Polyester-based polyurethanes exhibit high mechanical strength and adhesive properties, but their molecular backbone contains numerous ester bonds, making them susceptible to hydrolytic degradation in prolonged humid, high-temperature, or acidic / alkaline environments. Furthermore, the carboxylic acids generated during hydrolysis have an autocatalytic effect, accelerating chain segment breakage and leading to decreased adhesive strength, interfacial peeling, or even adhesive failure. Polyether-based polyurethanes offer good hydrolysis resistance, but their low molecular polarity generally results in insufficient adhesive strength and poor heat resistance. Polycarbonate-based polyurethanes combine good mechanical properties with hydrolysis resistance, making them a more ideal choice for soft segments. However, their cost is relatively high, and their crosslinking density is limited in conventional linear chain-extended systems. Under long-term humid and hot conditions, the interfacial bonding strength will gradually weaken, making it difficult to fully guarantee durability.

[0004] To improve the overall performance of polyurethane shoe adhesives, existing technologies typically modify them by increasing the hard segment content, introducing crosslinking agents, or adding inorganic nanofillers. Small-molecule anti-hydrolysis agents and antioxidants are also sometimes added to the system. However, increasing the hard segment content can easily lead to embrittlement and decreased flexibility of the adhesive layer; the network structure formed by traditional crosslinking systems is relatively simple, making it difficult to balance strength and durability; inorganic nanofillers generally suffer from insufficient dispersion stability, poor interfacial compatibility, and limited reinforcing efficiency; and additives exist in a physical blending form, lacking chemical bonds with the polyurethane backbone, and are prone to migration, precipitation, and loss with the aqueous phase during film formation and long-term use, causing the anti-hydrolysis function to decay over time and become unsustainable. Furthermore, conventional adhesive film surfaces lack a stable low surface energy barrier, allowing water molecules to easily penetrate and attack ester and urea bonds, further weakening interfacial adhesion and resistance to damp heat aging. Therefore, this invention provides a high-strength, hydrolysis-resistant polyurethane shoe adhesive and its preparation method to solve the aforementioned technical problems. Summary of the Invention

[0005] The purpose of this invention is to provide a high-strength, hydrolysis-resistant polyurethane shoe adhesive and its preparation method. The obtained polyurethane shoe adhesive has excellent bonding strength, hydrolysis resistance, damp heat aging resistance and interfacial adhesion, which can meet the high reliability bonding requirements of shoe materials under long-term service conditions.

[0006] To achieve the above objectives, the present invention provides a method for preparing a high-strength, hydrolysis-resistant polyurethane shoe adhesive, comprising the following steps:

[0007] (1) Heat the polymer polyol to 110-120℃, dehydrate it at -0.095~-0.098MPa for 1.5-2h, cool it down to 65-75℃ under nitrogen protection, add diisocyanate and dibutyltin dilaurate, and react at 70-80℃ for 2-3h; separately, predissolve 2,2-dimethylolpropionic acid in N-methylpyrrolidone, add it dropwise to the above system within 30-40min, continue to react at 70-75℃ for 1-2h, cool the system down to 50-55℃, add acetone in batches at 300-350rpm to dilute and reduce viscosity, and obtain polyurethane prepolymer acetone solution;

[0008] (2) Cool the polyurethane prepolymer obtained in step (1) to 45-50℃, add triethylamine to neutralize for 15-30 min, and then add polyether modified siloxane defoamer; slowly add deionized water under high shear at 1800-2500 rpm, and emulsify by reverse conversion for 30-40 min to obtain a stable polyurethane dispersion; after emulsification, dilute the linear polyamine chain extender with 1-5 times the mass of deionized water and add it dropwise with strong stirring, and extend the chain at 40-45℃ for 10-20 min; then add fluorosilicone modified hyperbranched amino alcohol crosslinking agent, and continue to react at 40-45℃ for 20-40 min; then add borate ester reinforcing agent dispersion, stir at 35-40℃ for 30-60 min, and finally remove acetone by vacuum distillation to obtain high-strength hydrolysis resistant polyurethane shoe adhesive.

[0009] Preferably, the amounts of each raw material, by weight, are as follows: 80-120 parts of polymeric polyol, 30-50 parts of diisocyanate, 0.05-0.20 parts of organotin catalyst, 4-6 parts of 2,2-dimethylolpropionic acid, 8-15 parts of N-methylpyrrolidone, 20-40 parts of acetone, 3-6 parts of tertiary amine neutralizer, 0.1-0.3 parts of defoamer, 150-250 parts of deionized water, 1-6 parts of linear polyamine chain extender, 8-20 parts of fluorosilicone modified hyperbranched amino alcohol crosslinking agent, and 2-8 parts of borate ester reinforcing agent.

[0010] Preferably, the polymeric polyol is selected from one or more of polycarbonate diol, polytetrahydrofuran diol, and polycaprolactone diol, and the polycarbonate diol accounts for 40-90% of the total polymeric polyol; the diisocyanate is selected from one or more of isophorone diisocyanate, 4,4′-dicyclohexylmethane diisocyanate, and hexamethylene diisocyanate; and the linear polyamine chain extender is selected from one or more of isophorone diamine, ethylenediamine, diethylenetriamine, and hexamethylenediamine.

[0011] Preferably, the high-strength hydrolysis-resistant polyurethane shoe adhesive further includes 0.1-0.5 parts of leveling agent and 0.2-1 parts of antioxidant, wherein the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076 and antioxidant 168.

[0012] Preferably, the preparation step of the fluorosilicone modified hyperbranched polyamine crosslinking agent in step (2) is as follows:

[0013] S1. Disperse 1H,1H,2H,2H-perfluorohexanol and allyl bromide in anhydrous toluene, add anhydrous potassium carbonate and tetrabutylammonium bromide, and react at 60-70℃ for 6-8h under nitrogen protection. After the reaction is complete, cool and filter to remove inorganic salts. Wash the filtrate with water until neutral, separate the liquid, and desolvent under reduced pressure to obtain fluorinated allyl ether monomer.

[0014] S2. Add polymethylhydrosiloxane to the reactor, add 1 wt% isopropanol chloroplatinic acid solution under nitrogen protection, heat to 75-85℃, slowly add fluorinated allyl ether monomer, keep the reaction at the temperature for 2-3 hours, then add allyl glycidyl ether, stir the reaction at 80-85℃ for 3-4 hours, finally add allyl alcohol polyoxyethylene ether, continue the reaction for 1-2 hours, and obtain the terminal epoxy fluorosilicone intermediate by decolorization with activated carbon and vacuum de-volatilization.

[0015] S3. Dissolve hyperbranched polyethyleneimine in anhydrous ethanol, slowly add terminal epoxy fluorosilicone intermediate at 30-40℃, react at 35-45℃ for 8-10 hours after addition, and then remove solvent under reduced pressure to obtain the target crosslinking agent.

[0016] Preferably, by weight, step S1 includes 30-50 parts of 1H,1H,2H,2H-perfluorohexanol, 15-30 parts of allyl bromide, 100-150 parts of anhydrous toluene, 15-30 parts of anhydrous potassium carbonate, and 0.5-2 parts of tetrabutylammonium bromide.

[0017] Preferably, by weight, step S2 comprises 10-25 parts of polymethylhydrosiloxane, 0.05-0.15 parts of 1wt% isopropanol chloroplatinate solution, 20-40 parts of fluorinated allyl ether monomer, 10-25 parts of allyl glycidyl ether, and 5-15 parts of allyl alcohol polyoxyethylene ether; and step S3 comprises 10-20 parts of hyperbranched polyethyleneimine, 50-80 parts of anhydrous ethanol, and 40-80 parts of terminal epoxy group fluorosilicone intermediate.

[0018] Preferably, the preparation step of the borate ester reinforcing agent in step (2) is as follows:

[0019] A1. Add 3,4-dihydroxybenzoic acid, anhydrous DMF, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to a reaction vessel, activate at 25-30℃ for 30-35 min under nitrogen protection and in the dark, then add polypropylene glycol and react at 40-50℃ for 8-10 h. After filtration to remove precipitate, wash with water until neutral, and desolvent under reduced pressure to obtain catecholized polyether intermediate.

[0020] A2. The catechinized polyether intermediate, anhydrous ethanol and hydrophobic nano silica are dispersed at high speed of 8000-12000 for 2-3 hours at room temperature. 3-aminophenylboronic acid and 3A molecular sieve are added and reacted at 50-70℃ for 4-8 hours. After desolventizing under reduced pressure and vacuum drying, the target reinforcing agent is obtained.

[0021] Preferably, by weight, step A1 comprises 20-40 parts of 3,4-dihydroxybenzoic acid, 80-150 parts of anhydrous N,N-dimethylformamide, 6-20 parts of dicyclohexylcarbodiimide, 0.1-0.3 parts of 4-dimethylaminopyridine, and 20-40 parts of polypropylene glycol; and step A2 comprises 20-50 parts of catecholized polyether intermediate, 50-120 parts of anhydrous ethanol, 5-15 parts of hydrophobic nano-silica, 2-10 parts of 3-aminophenylboronic acid, and 10-30 parts of 3A molecular sieve.

[0022] The present invention also provides a high-strength hydrolysis-resistant polyurethane shoe adhesive prepared by any of the above preparation methods.

[0023] 1. This invention effectively solves the problems of hydrolytic degradation and strength decline caused by the easy absorption of water by polar groups in traditional waterborne polyurethane shoe adhesives by introducing a fluorosilicone-modified hyperbranched amino alcohol crosslinking agent to participate in the multi-level network construction of polyurethane dispersions. This crosslinking agent, leveraging the high-density functional groups of its hyperbranched active structure, undergoes deep chain extension crosslinking with polyurethane macromolecular segments during curing, forming a three-dimensional network structure that significantly improves the cohesive strength and mechanical strength of the resin matrix. Simultaneously, the modified fluorinated and siloxane segments in the crosslinking agent structure, due to their extremely low surface energy, spontaneously migrate and accumulate to the film surface during film formation, constructing a dense hydrophobic shielding layer. This synergistic physicochemical mechanism of high-strength internal crosslinking and strong external water repellency cuts off the capillary penetration path of external water molecules, effectively blocking the attack of water molecules on the ester and urea bonds in the polyurethane backbone, thereby achieving a significant improvement in the long-term hydrolysis resistance of the shoe adhesive.

[0024] 2. This invention incorporates a borate ester reinforcing agent synthesized from catecholized polyether intermediates, hydrophobic nano-silica, and aminophenylboronic acid. This reinforcing agent, through the dynamic borate ester bonds formed by the condensation of catechol and phenylboronic acid, the reactivity of the aminophenylboronic acid end groups, and the rigid reinforcing effect of the hydrophobic nano-silica, forms a synergistic system of dynamic covalent crosslinking and nano-interface reinforcement. This effectively overcomes the problems of insufficient dispersion stability, poor interfacial compatibility, and limited reinforcing efficiency of inorganic nanofillers. Specifically, the dynamic borate ester bonds are reversible covalent bonds, capable of reversible dissociation and reconstruction under stress or aging damage, imparting stress dissipation and a certain degree of self-healing ability to the adhesive film. The aminophenylboronic acid end groups can form additional binding sites with the hydroxyl groups in the substrate and polyurethane network. The hydrophobic nano-silica, after being modified by catecholized polyether coating, is dispersed stably and anchored in the reinforcing phase, providing rigid reinforcement. The synergistic effect of these three components significantly improves tensile strength and peel strength while further hindering moisture penetration, effectively ensuring the interfacial adhesion and durability of the shoe adhesive under long-term humid and hot service conditions.

[0025] 3. This invention utilizes polycarbonate diol as the main soft segment, supplemented with polytetrahydrofuran diol and polycaprolactone diol. The mixture undergoes chain extension with diisocyanate and the introduction of hydrophilic carboxyl groups with 2,2-dimethylolpropionic acid. Following neutralization with tertiary amines and phase inversion emulsification, a self-emulsifying waterborne polyurethane dispersion is constructed. This dispersion is then sequentially chain-extended with linear polyamines, cross-linked with fluorosilicone-modified hyperbranched amino alcohol cross-linking agents, and reinforced with borate ester reinforcing agents. This process combines optimized soft segments, hydrophilic self-emulsification, stepwise chain extension and cross-linking, and synergistic reinforcement. Through the synergistic effect of soft segment selection and functional additives, this process effectively overcomes the problem of existing waterborne polyurethane shoe adhesives failing to simultaneously achieve high adhesive strength and hydrolysis resistance. By replacing easily hydrolyzable adipate bonds with hydrolyzable carbonate bonds as the main soft segment structure, the sensitivity of the soft segments to wet and hot water hydrolysis is reduced at the molecular skeleton level. Furthermore, the combination of polyether and polyester soft segments adjusts the flexibility and crystallinity of the soft segments, resulting in a shoe adhesive that possesses both high cohesive strength and moderate initial tack. Detailed Implementation

[0026] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0027] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the experimental materials used, unless otherwise specified, were all purchased from conventional biochemical reagent stores. All quantitative experiments in the following examples were performed in triplicate, and the data are the average of the three replicates or the average ± standard deviation.

[0028] Polycarbonate diol, purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd., item number: PB11059, molecular weight 1000-2000;

[0029] Polytetrahydrofuran diol, purchased from Hubei Xinkang Pharmaceutical Chemical Co., Ltd., CAS No. ;

[0030] Polycaprolactone diol, purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd., item number: PC93880;

[0031] Polyether-modified siloxane defoamer, namely BYK-024, was purchased from Foshan Kening New Materials Co., Ltd., item number: KMT-2017;

[0032] The leveling agent, BYK-333, was purchased from Wuhan Rongcan Biotechnology Co., Ltd.

[0033] Antioxidant 1010 and Antioxidant 1076 were purchased from Hubei Yongkuo Technology Co., Ltd.

[0034] Antioxidant 168 was purchased from Wuhan Jiangxin Biotechnology Co., Ltd.

[0035] Polymethylhydrosiloxane, purchased from Wuhan Kanos Technology Co., Ltd., CAS No. ;

[0036] Hyperbranched polyethyleneimine, with an average molecular weight of approximately 600-1200, was purchased from Xi'an Qiyue Biotechnology Co., Ltd.

[0037] Polypropylene glycol, purchased from Shanghai Xuanya Biotechnology Co., Ltd., product number XY25125;

[0038] Hydrophobic nano-silica, purchased from Hubei Huifu Nanomaterials Co., Ltd., with a particle size of 10-20 nm and a specific surface area of ​​200-400 m². 2 / g;

[0039] 3A molecular sieve, purchased from Jiangsu Congzhong Chemical Co., Ltd.

[0040] Example 1

[0041] This embodiment provides a method for preparing high-strength, hydrolysis-resistant polyurethane shoe adhesive, using the following technical solution:

[0042] (1) Heat 32 parts of polycarbonate diol and 48 parts of polytetrahydrofuran diol to 110°C, stir at 120 rpm, dehydrate at -0.095 for 2 h, cool down to 65°C under nitrogen protection, add 30 parts of isophorone diisocyanate and 0.05 parts of dibutyltin dilaurate, and react at 70°C and 200 rpm for 3 h; separately, dissolve 4 parts of 2,2-dimethylolpropionic acid in 8 parts of N-methylpyrrolidone, add dropwise to the above system within 40 min, continue to react at 70°C for 2 h, cool the system to 50°C, and add 20 parts of acetone in batches at 300 rpm to dilute and reduce viscosity to obtain polyurethane prepolymer acetone solution;

[0043] (2) Cool the polyurethane prepolymer obtained in step (1) to 45°C, add 3 parts of triethylamine to neutralize for 30 min, and then add 0.1 parts of polyether modified siloxane defoamer; slowly add 150 parts of deionized water under high shear at 1800 rpm, and emulsify by reverse conversion for 40 min to obtain a stable polyurethane dispersion; after emulsification, dilute 1 part of ethylenediamine with 3 parts of deionized water, add dropwise under strong stirring at 600 rpm, and extend the chain at 40°C for 20 min; then add 8 parts of fluorosilicone modified hyperbranched amino alcohol crosslinking agent, and react at 400 rpm and 40°C for 40 min; separately disperse 2 parts of borate ester reinforcing agent in 6 parts of deionized water to obtain reinforcing agent dispersion, add it to the system, and stir at 300 rpm and 35°C for 60 min; add 0.1 parts of leveling agent and 0.2 parts of antioxidant 1010, and remove acetone under reduced pressure to obtain high-strength hydrolysis resistant polyurethane shoe adhesive.

[0044] The preparation steps of the fluorosilicone modified hyperbranched polyamine crosslinking agent in step (2) are as follows:

[0045] S1. Disperse 30 parts of 1H,1H,2H,2H-perfluorohexanol and 15 parts of allyl bromide in 100 parts of anhydrous toluene, add 15 parts of anhydrous potassium carbonate and 0.5 parts of tetrabutylammonium bromide, and react at 60°C for 8 hours under nitrogen protection and stirring at 200 rpm. After the reaction is complete, cool and filter to remove inorganic salts. Wash the filtrate with water until neutral, separate the liquid, and desolvent under reduced pressure to recover the solvent to obtain the fluorinated allyl ether monomer.

[0046] S2. Add 10 parts of polymethylhydrosiloxane to the reactor, under nitrogen protection and stirring at 150 rpm, add 0.05 parts of 1wt% isopropanol chloroplatinate solution, heat to 75℃, slowly add 20 parts of fluorinated allyl ether monomer, keep the reaction at this temperature for 3 hours, then add 10 parts of allyl glycidyl ether, react at 80℃ for 4 hours, finally add 5 parts of allyl alcohol polyoxyethylene ether, continue the reaction for 2 hours, and obtain the terminal epoxy fluorosilicone intermediate by decolorization with activated carbon and vacuum de-devouring.

[0047] S3. Dissolve 10 parts of hyperbranched polyethyleneimine in 50 parts of anhydrous ethanol, stir at 200 rpm, and slowly add 40 parts of terminal epoxy fluorosilicone intermediate at 35°C. After the addition is complete, react at 35°C for 10 h, and then remove the solvent under reduced pressure to obtain the target crosslinking agent.

[0048] The preparation steps of the borate ester reinforcing agent in step (2) are as follows:

[0049] A1. Add 20 parts of 3,4-dihydroxybenzoic acid, 80 parts of anhydrous DMF, 6 parts of dicyclohexylcarbodiimide and 0.1 parts of 4-dimethylaminopyridine to a reaction vessel, under nitrogen protection and in the dark, and activate at 25°C for 35 min with stirring at 200 rpm. Then add 20 parts of polypropylene glycol and react at 40°C for 10 h. After filtration to remove precipitate, wash with water until neutral, and desolvent under reduced pressure to obtain catecholized polyether intermediate.

[0050] A2. 20 parts of catecholized polyether intermediate, 50 parts of anhydrous ethanol and 5 parts of hydrophobic nano silica were dispersed at 8000 rpm for 3 h at room temperature. 2 parts of 3-aminophenylboronic acid and 10 parts of 3A molecular sieve were added and reacted at 50 °C for 8 h. After desolventizing under reduced pressure and drying under vacuum, the target reinforcing agent was obtained.

[0051] Example 2

[0052] This embodiment provides a method for preparing high-strength, hydrolysis-resistant polyurethane shoe adhesive, using the following technical solution:

[0053] (1) Heat 54 parts of polycarbonate diol and 36 parts of polytetrahydrofuran diol to 113°C, stir at 130 rpm, dehydrate at −0.096 MPa for 1.8 h, cool down to 68°C under nitrogen protection, add 36 parts of isophorone diisocyanate and 0.1 parts of dibutyltin dilaurate, and react at 73°C at 250 rpm for 2.5 h; separately, dissolve 4.5 parts of 2,2-dimethylolpropionic acid in 10 parts of N-methylpyrrolidone, add dropwise to the above system within 35 min, continue to react at 72°C for 1.5 h, cool the system to 52°C, and add 26 parts of acetone in batches at 320 rpm to dilute and reduce viscosity to obtain polyurethane prepolymer acetone solution;

[0054] (2) Cool the polyurethane prepolymer obtained in step (1) to 46°C, add 4 parts of triethylamine, neutralize at 180 rpm for 25 min, and then add 0.15 parts of polyether modified siloxane defoamer; slowly add 180 parts of deionized water under high shear at 2000 rpm, and emulsify by reverse conversion for 35 min to obtain a stable dispersion; after emulsification, dilute 2.5 parts of isophorone diamine with 7.5 parts of deionized water, add dropwise under strong stirring at 650 rpm, and extend the chain at 42°C for 18 min; then add 11 parts of fluorosilicone modified hyperbranched amino alcohol crosslinking agent, and react at 450 rpm and 42°C for 35 min; separately disperse 4 parts of borate ester reinforcing agent in 10 parts of deionized water to obtain reinforcing agent dispersion, add it to the system, and stir at 350 rpm and 37°C for 50 min; add 0.2 parts of leveling agent and 0.4 parts of antioxidant 1076, and remove acetone under reduced pressure to obtain high-strength hydrolysis resistant polyurethane shoe adhesive.

[0055] The preparation steps of the fluorosilicone modified hyperbranched polyamine crosslinking agent in step (2) are as follows:

[0056] S1. 36 parts of 1H,1H,2H,2H-perfluorohexanol and 19 parts of allyl bromide were dispersed in 115 parts of anhydrous toluene. 19 parts of anhydrous potassium carbonate and 0.9 parts of tetrabutylammonium bromide were added. The mixture was reacted at 63°C for 7.5 h under nitrogen protection and stirring at 250 rpm. After the reaction was completed, the mixture was cooled, filtered to remove inorganic salts, and the filtrate was washed with water until neutral. The mixture was separated, and the solvent was recovered under reduced pressure to obtain the fluorinated allyl ether monomer.

[0057] S2. Add 14 parts of polymethylhydrosiloxane to the reactor, under nitrogen protection and stirring at 180 rpm, add 0.08 parts of 1wt% isopropanol chloroplatinate solution, and heat to 78℃; slowly add 26 parts of fluorinated allyl ether monomer, and keep the reaction at this temperature for 2.5 h; then add 14 parts of allyl glycidyl ether, and react at 82℃ for 3.5 h; finally, add 8 parts of allyl alcohol polyoxyethylene ether for end capping, and continue the reaction for 1.5 h. After decolorization with activated carbon and vacuum devolatilization, the terminal epoxy fluorosilicone intermediate is obtained.

[0058] S3. Dissolve 13 parts of hyperbranched polyethyleneimine in 60 parts of anhydrous ethanol, stir at 250 rpm, and slowly add 52 parts of terminal epoxy fluorosilicone intermediate at 33°C. After the addition is complete, react at 38°C for 9.5 h, and then remove the solvent under reduced pressure to obtain the target crosslinking agent.

[0059] The preparation steps of the borate ester reinforcing agent in step (2) are as follows:

[0060] A1. 26 parts of 3,4-dihydroxybenzoic acid, 100 parts of anhydrous DMF, 10 parts of dicyclohexylcarbodiimide and 0.15 parts of 4-dimethylaminopyridine were added to a reaction vessel. Under nitrogen protection and in the dark, the mixture was activated at 27°C for 33 min with stirring at 250 rpm. Then, 26 parts of polypropylene glycol were added, and the reaction was carried out at 43°C for 9.5 h. After filtration to remove precipitate, the mixture was washed with water until neutral, and then dissolved under reduced pressure to obtain a catecholized polyether intermediate.

[0061] A2. 28 parts of catecholized polyether intermediate, 70 parts of anhydrous ethanol and 8 parts of hydrophobic nano silica were dispersed at 9000 rpm for 2.5 h at room temperature. 4 parts of 3-aminophenylboronic acid and 16 parts of 3A molecular sieve were added. The mixture was stirred at 350 rpm and reacted at 57 °C for 7 h. After desolventizing under reduced pressure and vacuum drying, the target reinforcing agent was obtained.

[0062] Example 3

[0063] This embodiment provides a method for preparing high-strength, hydrolysis-resistant polyurethane shoe adhesive, using the following technical solution:

[0064] (1) Heat 108 parts of polycarbonate diol and 12 parts of polycaprolactone diol to 120°C, stir at 150 rpm, dehydrate at −0.098 MPa for 1.5 h, cool down to 75°C under nitrogen protection, add 50 parts of 4,4'-dicyclohexylmethane diisocyanate and 0.20 parts of dibutyltin dilaurate, and react at 80°C at 300 rpm for 2 h; separately, predissolve 6 parts of 2,2-dimethylolpropionic acid in 15 parts of N-methylpyrrolidone, add dropwise to the above system within 30 min, continue to react at 75°C for 1 h, cool the system to 55°C, and add 40 parts of acetone in batches at 350 rpm to dilute and reduce viscosity to obtain polyurethane prepolymer acetone solution;

[0065] (2) Cool the polyurethane prepolymer obtained in step (1) to 50°C, add 6 parts of triethylamine, neutralize at 220 rpm for 15 min, and then add 0.3 parts of polyether modified siloxane defoamer; slowly add 250 parts of deionized water under high shear at 2500 rpm, and emulsify by reverse conversion for 30 min to obtain a stable dispersion; after emulsification, dilute 6 parts of hexamethylenediamine with 30 parts of deionized water, add dropwise under strong stirring at 750 rpm, and extend the chain at 45°C for 10 min; then add 20 parts of fluorosilicone modified hyperbranched amino alcohol crosslinking agent, and react at 550 rpm and 45°C for 20 min; separately disperse 8 parts of borate ester reinforcing agent in 16 parts of deionized water to obtain reinforcing agent dispersion, add it to the system, and stir at 450 rpm and 40°C for 30 min; add 0.5 parts of leveling agent and 1 part of antioxidant 168, and remove acetone under reduced pressure to obtain high-strength hydrolysis resistant polyurethane shoe adhesive.

[0066] The preparation steps of the fluorosilicone modified hyperbranched polyamine crosslinking agent in step (2) are as follows:

[0067] S1. Disperse 50 parts of 1H,1H,2H,2H-perfluorohexanol and 30 parts of allyl bromide in 150 parts of anhydrous toluene, add 30 parts of anhydrous potassium carbonate and 2 parts of tetrabutylammonium bromide, and react at 70°C for 6 hours under nitrogen protection and stirring at 300 rpm. After the reaction is completed, cool and filter to remove inorganic salts. Wash the filtrate with water until neutral, separate the liquid, and desolvent under reduced pressure to recover the solvent to obtain the fluorinated allyl ether monomer.

[0068] S2. Add 25 parts of polymethylhydrosiloxane to the reactor, under nitrogen protection and stirring at 220 rpm, add 0.15 parts of 1wt% isopropanol chloroplatinate solution, heat to 85℃, slowly add 40 parts of fluorinated allyl ether monomer, keep the reaction at the temperature for 2 hours, then add 25 parts of allyl glycidyl ether, react at 85℃ for 3 hours, finally add 15 parts of allyl alcohol polyoxyethylene ether for end capping, continue the reaction for 1 hour, and obtain the terminal epoxy fluorosilicone intermediate by decolorization with activated carbon and vacuum de-volatilization.

[0069] S3. Dissolve 20 parts of hyperbranched polyethyleneimine in 80 parts of anhydrous ethanol, stir at 300 rpm, and slowly add 80 parts of terminal epoxy fluorosilicone intermediate at 40°C. After the addition is complete, react at 45°C for 8 hours, and then remove the solvent under reduced pressure to obtain the target crosslinking agent.

[0070] The preparation steps of the borate ester reinforcing agent in step (2) are as follows:

[0071] A1. Add 40 parts of 3,4-dihydroxybenzoic acid, 150 parts of anhydrous DMF, 20 parts of dicyclohexylcarbodiimide and 0.3 parts of 4-dimethylaminopyridine to a reaction vessel, under nitrogen protection and in the dark, and activate at 30°C for 30 min with stirring at 300 rpm. Then add 40 parts of polypropylene glycol and react at 50°C for 8 h. After filtration to remove precipitate, wash with water until neutral, and desolvent under reduced pressure to obtain catecholized polyether intermediate.

[0072] A2. 50 parts of catecholized polyether intermediate, 120 parts of anhydrous ethanol and 15 parts of hydrophobic nano silica were dispersed at 12,000 rpm for 2 hours at room temperature. 10 parts of 3-aminophenylboronic acid and 30 parts of 3A molecular sieve were added. The mixture was stirred at 450 rpm and reacted at 70°C for 4 hours. After desolventizing under reduced pressure and vacuum drying, the target reinforcing agent was obtained.

[0073] Example 4

[0074] This embodiment provides a method for preparing high-strength, hydrolysis-resistant polyurethane shoe adhesive, using the following technical solution:

[0075] (1) Heat 80 parts of polycarbonate diol and 20 parts of polycaprolactone diol to 115°C, stir at 140 rpm, dehydrate at −0.097 MPa for 1.5 h, cool down to 70°C under nitrogen protection, add 42 parts of 4,4'-dicyclohexylmethane diisocyanate and 0.12 parts of dibutyltin dilaurate, and react at 78°C at 280 rpm for 2 h; separately, predissolve 5 parts of 2,2-dimethylolpropionic acid in 12 parts of N-methylpyrrolidone, add dropwise to the above system within 30 min, continue to react at 73°C for 1.5 h, cool the system to 53°C, and add 32 parts of acetone in batches at 340 rpm to dilute and reduce viscosity to obtain polyurethane prepolymer acetone solution;

[0076] (2) Cool the polyurethane prepolymer obtained in step (1) to 48°C, add 5 parts of triethylamine, neutralize at 200 rpm for 20 min, and then add 0.2 parts of polyether modified siloxane defoamer; slowly add 200 parts of deionized water under high shear at 2300 rpm, and emulsify by reverse conversion for 30 min to obtain a stable dispersion; after emulsification, dilute 3.5 parts of isophorone diamine with 14 parts of deionized water, add dropwise under strong stirring at 700 rpm, and extend the chain at 44°C for 12 min; then add 16 parts of fluorosilicone modified hyperbranched amino alcohol crosslinking agent, and react at 500 rpm and 44°C for 25 min; separately disperse 6 parts of borate ester reinforcing agent in 14 parts of deionized water to obtain reinforcing agent dispersion, add it to the system, and stir at 420 rpm and 39°C for 40 min; add 0.3 parts of leveling agent and 0.6 parts of antioxidant 1010, and remove acetone under reduced pressure to obtain high-strength hydrolysis resistant polyurethane shoe adhesive.

[0077] The preparation steps of the fluorosilicone modified hyperbranched polyamine crosslinking agent in step (2) are as follows:

[0078] S1. 42 parts of 1H,1H,2H,2H-perfluorohexanol and 25 parts of allyl bromide were dispersed in 130 parts of anhydrous toluene. 25 parts of anhydrous potassium carbonate and 1.5 parts of tetrabutylammonium bromide were added. The mixture was reacted at 68°C for 6.5 h under nitrogen protection and stirring at 280 rpm. After the reaction was completed, the mixture was cooled, filtered to remove inorganic salts, and the filtrate was washed with water until neutral. The mixture was separated, and the solvent was recovered under reduced pressure to obtain the fluorinated allyl ether monomer.

[0079] S2. Add 18 parts of polymethylhydrosiloxane to the reactor, under nitrogen protection and stirring at 200 rpm, add 0.12 parts of 1wt% isopropanol chloroplatinate solution, heat to 83℃, slowly add 33 parts of fluorinated allyl ether monomer, and keep the reaction at this temperature for 2.5 h; then add 18 parts of allyl glycidyl ether, react at 84℃ for 3 h, finally add 10 parts of allyl alcohol polyoxyethylene ether for end capping, and continue the reaction for 1.5 h. After decolorization with activated carbon and vacuum devolatilization, the terminal epoxy fluorosilicone intermediate is obtained.

[0080] S3. Dissolve 16 parts of hyperbranched polyethyleneimine in 70 parts of anhydrous ethanol, stir at 280 rpm, and slowly add 65 parts of terminal epoxy fluorosilicone intermediate at 38°C. After the addition is complete, react at 43°C for 8.5 h, and then remove solvent under reduced pressure to obtain the target crosslinking agent.

[0081] The preparation steps of the borate ester reinforcing agent in step (2) are as follows:

[0082] A1. 32 parts of 3,4-dihydroxybenzoic acid, 120 parts of anhydrous DMF, 15 parts of dicyclohexylcarbodiimide and 0.2 parts of 4-dimethylaminopyridine were added to a reaction vessel. Under nitrogen protection and in the dark, the mixture was activated at 28°C for 32 min with stirring at 280 rpm. Then, 32 parts of polypropylene glycol were added and the reaction was carried out at 48°C for 8.5 h. After filtration to remove precipitate, the mixture was washed with water until neutral and dissolved under reduced pressure to obtain a catecholized polyether intermediate.

[0083] A2. 40 parts of catecholized polyether intermediate, 100 parts of anhydrous ethanol and 12 parts of hydrophobic nano silica were dispersed at 11,000 rpm for 2.5 h at room temperature. 8 parts of 3-aminophenylboronic acid and 24 parts of 3A molecular sieve were added. The mixture was stirred at 420 rpm and reacted at 65 °C for 5 h. After desolventizing under reduced pressure and vacuum drying, the target reinforcing agent was obtained.

[0084] Comparative Example 1

[0085] The difference between this comparative example and Example 4 is that: in step (2), no fluorosilicone modified hyperbranched amino alcohol crosslinking agent was added, that is, after the emulsification and chain extension were completed, no fluorosilicone modified hyperbranched amino alcohol crosslinking agent was added and the borate ester reinforcing agent dispersion was directly reinforced. Other conditions were the same as in Example 4.

[0086] Comparative Example 2

[0087] The difference between this comparative example and Example 4 is that: in step (2), no borate ester reinforcing agent dispersion was added, that is, after crosslinking with fluorosilicone modified hyperbranched amino alcohol crosslinking agent, no reinforcing agent dispersion prepared by borate ester reinforcing agent dispersion was added and acetone was directly removed by vacuum evaporation. Other conditions were the same as in Example 4.

[0088] Comparative Example 3

[0089] The difference between this comparative example and Example 4 is that step S1 is omitted in the preparation of the fluorosilicone modified hyperbranched amino alcohol crosslinking agent, that is, the fluorinated allyl ether monomer is not prepared. In step S2, the fluorinated allyl ether monomer is not added dropwise, but polymethylhydrosiloxane is reacted sequentially with allyl glycidyl ether and allyl alcohol polyoxyethylene ether. Then, in step S3, the hyperbranched amino alcohol crosslinking agent without fluorine segments is obtained by ring-opening addition with hyperbranched polyethyleneimine. Other conditions are the same as in Example 4.

[0090] Comparative Example 4

[0091] The difference between this comparative example and Example 4 is that step S3 is omitted in the preparation process of the fluorosilicone modified hyperbranched amino alcohol crosslinking agent. That is, only steps S1 and S2 are completed to obtain the terminal epoxy fluorosilicone intermediate, and the terminal epoxy fluorosilicone intermediate is directly used as a crosslinking agent for the crosslinking treatment in step (2) without undergoing ring-opening addition with hyperbranched polyethyleneimine. Other conditions are the same as in Example 4.

[0092] Comparative Example 5

[0093] The difference between this comparative example and Example 4 is that step A1 is omitted in the preparation of the borate ester reinforcing agent, that is, the catecholized polyether intermediate is not prepared. In step A2, an equal amount of polypropylene glycol is used to replace the catecholized polyether intermediate and directly react with 3-aminophenylboronic acid and hydrophobic nano silica to obtain the reinforcing agent, so that the dynamic borate ester bond of condensation between catechol and phenylboronic acid is not formed in the system. Other conditions are the same as in Example 4.

[0094] Comparative Example 6

[0095] The difference between this comparative example and Example 4 is that the addition of 3-aminophenylboronic acid is omitted in the preparation of the borate ester reinforcing agent. That is, 3-aminophenylboronic acid is not added in step A2, and the reinforcing agent is prepared by dispersing the catecholized polyether intermediate with hydrophobic nano silica, so that dynamic borate bonds are not formed in the system. Other conditions are the same as in Example 4.

[0096] Performance testing

[0097] The polyurethane shoe adhesives prepared in Examples 1-4 and Comparative Examples 1-6 were uniformly coated onto the surfaces of natural rubber sheets and PVC sheets that had been sanded and cleaned with ethanol, with the coating amount controlled at 150-200 g / m². 2After the adhesive layer is dried at room temperature, it is activated at 60°C. Then, the two substrates are bonded together and a pressure of 0.3 MPa is applied for 2 minutes to obtain the bonded sample. The sample is placed at room temperature for 72 hours before performance testing.

[0098] 1. Peel strength test: The peel strength of the high-strength hydrolysis-resistant polyurethane shoe adhesives of Examples 1-4 and Comparative Examples 1-6 was tested according to GB / T2790-1995 standard. The test results are shown in Table 1.

[0099] 2. Tensile property test: The tensile strength of the high-strength hydrolysis-resistant polyurethane shoe adhesives of Examples 1-4 and Comparative Examples 1-6 was tested according to GB / T7124-2008 standard. The test results are shown in Table 1.

[0100] 3. Hydrolysis resistance: The prepared sample was completely immersed in deionized water at 70℃ for 7 days. After soaking, it was taken out and the surface moisture was dried with filter paper. The tensile strength was tested according to the above method, and the strength retention rate was calculated: Strength retention rate (%) = (tensile shear strength after soaking / tensile shear strength before soaking) × 100%. The test results are shown in Table 1.

[0101] 4. Resistance to damp heat aging: The sample was placed in a constant temperature and humidity chamber at 70℃ and 95% relative humidity for 72 hours. After being removed, it was placed at room temperature for 24 hours. The tensile strength was tested according to the above method, and the strength retention rate was calculated. The test results are shown in Table 1.

[0102] 5. Storage stability test: The polyurethane shoe adhesive sample was placed in a sealed glass bottle and stored at (25±2)℃ for 60 days. The results were observed to see if the sample showed stratification, precipitation, gelation or other phenomena. The test results are shown in Table 1.

[0103] Table 1

[0104] Example 1 18.3 6.2 83.5 80.1 Uniform appearance, no abnormalities Example 2 21.7 7.6 88.3 86.2 Uniform appearance, no abnormalities Example 3 24.1 9.1 91.6 89.4 Uniform appearance, no abnormalities Example 4 24.6 9.6 92.4 90.3 Uniform appearance, no abnormalities Comparative Example 1 10.8 2.9 61.7 57.3 Uniform appearance, no abnormalities Comparative Example 2 14.3 4.3 76.8 72.5 Uniform appearance, no abnormalities Comparative Example 3 17.4 5.7 73.4 71.9 Uniform appearance, no abnormalities Comparative Example 4 12.6 3.5 69.1 66.2 Uniform appearance, no abnormalities Comparative Example 5 15.1 4.8 79.5 75.6 There is slight sedimentation at the bottom. Comparative Example 6 16.2 5.2 81.2 77.8 Uniform appearance, no abnormalities

[0105] The high-strength hydrolysis-resistant polyurethane shoe adhesives prepared in Examples 1-4 exhibit excellent bonding strength and long-term durability. This is attributed to the synergistic effect of various functional components in the process. The use of hydrolysis-resistant carbonate bonds instead of easily hydrolyzable ester bonds as the soft segment main body weakens the sensitivity to damp heat at the molecular skeleton level. The fluorosilicone-modified hyperbranched amino alcohol crosslinking agent constructs a three-dimensional crosslinking network with the high-density functional groups of the hyperbranched structure to enhance the cohesive force of the matrix. It also forms a low surface energy hydrophobic barrier by migrating and enriching fluorine-containing and siloxane segments to the surface of the adhesive film. The borate ester reinforcing agent is synergistically enhanced by the stress dissipation of dynamic borate ester bonds, the interfacial adhesion of phenylboronic acid end groups, and the rigid reinforcement of catechol-coated modified nano-silica. Thus, the shoe adhesive maintains high strength while also having excellent resistance to hydrolysis and damp heat aging.

[0106] Comparative Example 1, lacking a fluorosilicone-modified hyperbranched amino alcohol crosslinking agent, only exhibited linear chain extension, lacking a three-dimensional crosslinking network and surface hydrophobic barrier, resulting in a simultaneous loss of cohesive strength and water repellency. Comparative Example 2, without the introduction of a borate ester reinforcing agent, retained a complete crosslinking network but lacked dynamic borate ester bonds, interfacial attachment points, and nano-rigid reinforcement, leading to a significant decline in strength and peel performance. Comparative Example 3, lacking fluorinated segments, had a complete crosslinking network but insufficient surface hydrophobic barrier, exhibiting particularly weak performance under humid and hot environments. Comparative Example 4, omitting the ring-opening addition of hyperbranched polyethyleneimine, used only a terminal epoxy-based fluorosilicone intermediate as the crosslinking agent, failing to construct a high-density network, resulting in a significant decrease in cohesive strength. Comparative Example 5, replacing catecholized polyether with polypropylene glycol, failed to form dynamic borate ester bonds and lost the anchoring and coating of nano-silica, causing filler agglomeration and stratified precipitation during storage, simultaneously weakening both reinforcing and stable performance. Comparative Example 6, without the addition of 3-aminophenylboronic acid, failed to form dynamic borate ester bonds, resulting in a lack of stress dissipation and interfacial bonding ability, thus disrupting the overall synergistic reinforcing system.

[0107] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-strength, hydrolysis-resistant polyurethane shoe adhesive, characterized in that, Includes the following steps: (1) The polymer polyol is heated to dehydrate, and reacted with diisocyanate and organotin catalyst under nitrogen protection to generate terminal isocyanate prepolymer. Then 2,2-dimethylolpropionic acid is added to carry out chain extension reaction. After the reaction is completed, acetone is added to dilute and reduce viscosity to obtain polyurethane prepolymer acetone solution. (2) The polyurethane prepolymer acetone solution obtained in step (1) is neutralized with tertiary amine and defoamer is added. Deionized water is added under high shear stirring to perform reverse emulsification to obtain polyurethane dispersion. Then, linear polyamine chain extender is added sequentially for chain extension, fluorosilicone modified hyperbranched amine alcohol crosslinking agent is added for crosslinking, and borate ester reinforcing agent dispersion is added for reinforcement treatment. Finally, acetone is removed by vacuum evaporation to obtain the high-strength hydrolysis resistant polyurethane shoe adhesive.

2. The preparation method according to claim 1, characterized in that, The amounts of each raw material, by weight, are as follows: 80-120 parts of polymer polyol, 30-50 parts of diisocyanate, 0.05-0.20 parts of organotin catalyst, 4-6 parts of 2,2-dimethylolpropionic acid, 8-15 parts of N-methylpyrrolidone, 20-40 parts of acetone, 3-6 parts of tertiary amine neutralizer, 0.1-0.3 parts of defoamer, 150-250 parts of deionized water, 1-6 parts of linear polyamine chain extender, 8-20 parts of fluorosilicone modified hyperbranched amino alcohol crosslinking agent, and 2-8 parts of borate ester reinforcing agent; the organotin catalyst is dibutyltin dilaurate, the tertiary amine neutralizer is triethylamine, and the defoamer is a polyether modified siloxane defoamer.

3. The preparation method according to claim 1 or 2, characterized in that, The polymer polyol is selected from one or more of polycarbonate diol, polytetrahydrofuran diol, and polycaprolactone diol, and the polycarbonate diol accounts for 40-90% of the total polymer polyol; the diisocyanate is selected from one or more of isophorone diisocyanate, 4,4′-dicyclohexylmethane diisocyanate, and hexamethylene diisocyanate; the linear polyamine chain extender is selected from one or more of isophorone diamine, ethylenediamine, diethylenetriamine, and hexamethylenediamine.

4. The preparation method according to claim 1, characterized in that, The high-strength hydrolysis-resistant polyurethane shoe adhesive also contains 0.1-0.5 parts of leveling agent and 0.2-1 parts of antioxidant, wherein the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076 and antioxidant 168.

5. The preparation method according to claim 1, characterized in that, The fluorosilicone-modified hyperbranched amino alcohol crosslinking agent is prepared by the following steps: S1. 1H,1H,2H,2H-perfluorohexanol and allyl bromide were dispersed in anhydrous toluene, anhydrous potassium carbonate and tetrabutylammonium bromide were added, and the mixture was reacted at 60-70℃ for 6-8 h under nitrogen protection. After cooling and filtration to remove inorganic salts, the filtrate was washed with water until neutral, separated, and then desolvated under reduced pressure to obtain fluorinated allyl ether monomer. S2. Add polymethylhydrosiloxane to the reactor, add isopropanol chloroplatinic acid solution under nitrogen protection and heat to 75-85℃, slowly add the fluorinated allyl ether monomer and keep the reaction at the temperature for 2-3 hours, then add allyl glycidyl ether dropwise and react at 80-85℃ for 3-4 hours, then add allyl alcohol polyoxyethylene ether and continue the reaction for 1-2 hours. After decolorization with activated carbon and vacuum devolatilization, the terminal epoxy fluorosilicone intermediate is obtained. S3. Dissolve hyperbranched polyethyleneimine in anhydrous ethanol, and slowly add the terminal epoxy group fluorosilicone intermediate at 30-40℃. After the addition is complete, react at 35-45℃ for 8-10 hours. After desolvation under reduced pressure, the fluorosilicone modified hyperbranched amino alcohol crosslinking agent is obtained.

6. The preparation method according to claim 5, characterized in that, By weight, step S1 includes 30-50 parts of 1H,1H,2H,2H-perfluorohexanol, 15-30 parts of allyl bromide, 100-150 parts of anhydrous toluene, 15-30 parts of anhydrous potassium carbonate, and 0.5-2 parts of tetrabutylammonium bromide.

7. The preparation method according to claim 5, characterized in that, By weight, step S2 comprises 10-25 parts of polymethylhydrosiloxane, 0.05-0.15 parts of 1wt% isopropanol chloroplatinate solution, 20-40 parts of fluorinated allyl ether monomer, 10-25 parts of allyl glycidyl ether, and 5-15 parts of allyl alcohol polyoxyethylene ether; step S3 comprises 10-20 parts of hyperbranched polyethyleneimine, 50-80 parts of anhydrous ethanol, and 40-80 parts of terminal epoxy group fluorosilicone intermediate.

8. The preparation method according to claim 1, characterized in that, The borate ester reinforcing agent is prepared by the following steps: A1. Add 3,4-dihydroxybenzoic acid, anhydrous N,N-dimethylformamide, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to a reaction vessel, activate at 25-30℃ for 30-35 min under nitrogen protection and in the dark, then add polypropylene glycol and react at 40-50℃ for 8-10 h. After filtration to remove the precipitate, wash with water until neutral, and desolvent under reduced pressure to obtain the catecholized polyether intermediate. A2. Catecholized polyether intermediate, anhydrous ethanol and hydrophobic nano silica are dispersed at high speed of 8000-12000 rpm for 2-3 hours at room temperature. 3-aminophenylboronic acid and 3A molecular sieve are added and reacted at 50-70℃ for 4-8 hours. After desolventizing under reduced pressure and vacuum drying, the borate ester reinforcing agent is obtained.

9. The preparation method according to claim 8, characterized in that, By weight, step A1 comprises 20-40 parts of 3,4-dihydroxybenzoic acid, 80-150 parts of anhydrous N,N-dimethylformamide, 6-20 parts of dicyclohexylcarbodiimide, 0.1-0.3 parts of 4-dimethylaminopyridine, and 20-40 parts of polypropylene glycol; step A2 comprises 20-50 parts of catecholized polyether intermediate, 50-120 parts of anhydrous ethanol, 5-15 parts of hydrophobic nano-silica, 2-10 parts of 3-aminophenylboronic acid, and 10-30 parts of 3A molecular sieve.

10. A high-strength, hydrolysis-resistant polyurethane shoe adhesive, characterized in that, It is prepared by any one of claims 1-9.